Oxidized low-density lipoprotein (LDL) and LDL cholesterol are associated with outcomes of minor stroke and TIA. (March 2020) - Wang, Anxin; Dai, Liye; Zhang, Nan; Lin, Jinxi; Chen, Guojuan; Zuo, Yingting; Li, Hao; Wang, Yilong; Meng, Xia; Wang, Yongjun
Abstract: Background and aims: Low-density lipoprotein (LDL) and oxidized low-density lipoprotein (oxLDL) levels are thought to be related to recurrent stroke. However, the joint association of circulating LDL and oxLDL levels with the outcomes of acute minor ischemic stroke and transient ischemic attack (TIA) remains unclear. The goal of the study was to evaluate whether LDL and oxLDL have a combined effect on outcomes of acute minor stroke and TIA. Methods: In the Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events (CHANCE) trial, a subgroup of 3019 patients with baseline oxLDL and LDL levels were analyzed. Patients were divided into four groups according to different combinations of LDL (LDL < 3.37 mmol/L, LDL ≥ 3.37 mmol/L) and oxLDL levels (oxLDL <13.96 μg/dL, oxLDL ≥ 13.96 μg/dL). The primary outcome was any stroke within 90 days. The secondary outcomes included any stroke within 1 year and ischemic stroke and combined vascular events within 90 days and 1 year. The poor functional outcome included modified Rankin Scale (mRS) 3–6 at 90-day and 12-month follow-up. The association of LDL and oxLDL with the prognosis of patients was examined using multivariable Cox regression models. Results: Among 3019 patients included in this study, the medians (interquartile range) of oxLDL and LDL were 13.96 (6.65–28.81) μg/dL and 3.1 (2.5–3.8) mmol/L, respectively. The cumulative occurrence of recurrent stroke, ischemic stroke, and combined vascular events was 9.74%, 9.54%, and 9.80% within 90 days of follow-up. Compared with those with low LDL and oxLDL levels (LDL < 3.37 mmol/L with oxLDL <13.96 μg/dL), patients with high levels of LDL and oxLDL (LDL ≥3.37 mmol/L, oxLDL ≥13.96 μg/dL) had significantly increased risk of recurrent stroke at 90 days (HR, 1.57; 95% CI, 1.10–2.24) and 1 year (HR, 1.49; 95% CI, 1.10–2.04). Patients in groups with LDL ≥3.37 mmol/L, oxLDL <13.96 μg/dL (HR, 1.35; 95% CI, 0.94–1.93) or LDL < 3.37 mmol/L with oxLDL ≥13.96 μg/dL (HR, 1.11; 95% CI, 0.77–1.59) showed no statistical difference for stroke recurrence. Similar results were found for functional outcomes. Conclusions: The presence of higher combined serum oxLDL and LDL levels was associated with increased risk of recurrent stroke and poor functional outcomes in minor stroke or high-risk TIA patients. Graphical abstract: Image 1 Highlights: The combination of oxLDL and LDL can predict recurrent stroke independently in patients with minor stroke or transient ischemic attack (TIA). The combination of oxLDL and LDL can also predict poor functional outcomes. Combined utility of oxLDL and LDL may be more useful in patients with minor stroke or TIA.